2007
DOI: 10.1002/jae.925
|View full text |Cite
|
Sign up to set email alerts
|

Efficient tests of long‐run causation in trivariate VAR processes with a rolling window study of the money–income relationship

Abstract: SUMMARYThis paper develops a simple sequential multiple-horizon non-causation test strategy for trivariate VAR models (with one auxiliary variable). We apply the test strategy to a rolling window study of money supply and real income, with the price of oil, the unemployment rate and the spread between the Treasury bill and commercial paper rates as auxiliary processes. Ours is the first study to control simultaneously for common stochastic trends, sensitivity of test statistics to the chosen sample period, nul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
1
26

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(95 citation statements)
references
References 42 publications
1
67
1
26
Order By: Relevance
“…Salamaliki and Venetis (2013) [4] argued that no previous studies took into account the indirect causality. To do so, they studied the causal relationships between energy consumption, real GDP and capital stock in the group of seven advanced countries by employing two recent methods of Dufour-Pelletier-Renault (2006) [26] and Hill (2007) [27] in order to detect direct and indirect causal effects. They found that in general, real GDP causes energy consumption for this group of countries.…”
mentioning
confidence: 99%
“…Salamaliki and Venetis (2013) [4] argued that no previous studies took into account the indirect causality. To do so, they studied the causal relationships between energy consumption, real GDP and capital stock in the group of seven advanced countries by employing two recent methods of Dufour-Pelletier-Renault (2006) [26] and Hill (2007) [27] in order to detect direct and indirect causal effects. They found that in general, real GDP causes energy consumption for this group of countries.…”
mentioning
confidence: 99%
“…The indirect part of the causality states that there might not be a direct impact of Y on X yet there can be an indirect impact through an auxiliary variable 'Z'; Y causes Z and further Z causes X. We have conducted efficient, non-causality tests to check the impact of Indian, Chinese and the US markets on each other during the crisis period, inspired by Hill (2007) strategy.…”
Section: Efficient Tests Of Causalitymentioning
confidence: 99%
“…Secondly, we have captured the cross market spillovers in the context of stock market returns and volatility in the form of an index creation. Thirdly, we have employed the VAR model for both the stock market returns and volatility along with Efficient tests proposed by Hill (2007). The results obtained from the TGARCH model have been further modelled into the VAR framework.…”
Section: Introductionmentioning
confidence: 99%
“…Insert The latter result can be considered as an example of what is referred to in Hill (2007) as "compression of information" when auxiliary variables are available, yet they are omitted from the model. More precisely, compression of information may arise when Y causes X within the truncated system but does not cause X within the complete system.…”
Section: -Var and 4-var) Based On This Approach This Causal E¤ect mentioning
confidence: 99%
“…What is the ability of economic policy uncertainty to predict output and employment, and how can this ability be a¤ected by the treatment of trends in the time series or the information set employed? 4 We consider the concept of multiple horizon causality we employ to be very important when examining the dynamic interrelationships between a set of time series, since it can reveal additional information on multiple causal channels and the presence of causal chains among the system variables (Lütkepohl 1993, Dufour and Renault 1998, Hill 2007, except for the case of bivariate 2 Chicago Board of Options and Exchange (CBOE) Market volatility index. 3 The multi-horizon causality concept is considered to be a generalized notion of standard impulse response analysis, since the latter considers only a small subset of the coe¢ cients of lagged variables in forecasts at greater horizons (Dufour and Renault 1998).…”
Section: Introductionmentioning
confidence: 99%